From a Content Delivery Portal to a Knowledge Management System for Standardized Cancer Documentation - Schlue, Danijela; Mate, Sebastian; Haier, Jörg; Kadioglu, Dennis; Prokosch, Hans-Ulrich; Breil, Bernhard (Studies in health technology and informatics, 2017)
Heterogeneous tumor documentation and its challenges of interpretation of medical terms lead to problems in analyses of data from clinical and epidemiological cancer registries. The objective of this project was to design, implement and improve a national content delivery portal for oncological terms. Data elements of existing handbooks and documentation sources were analyzed, combined and summarized by medical experts of different comprehensive cancer centers. Informatics experts created a generic data model based on an existing metadata repository. In order to establish a national knowledge management system for standardized cancer documentation, a prototypical tumor wiki was designed and implemented. Requirements engineering techniques were applied to optimize this platform. It is targeted to user groups such as documentation officers, physicians and patients. The linkage to other information sources like PubMed and MeSH was realized.
EVALuna2:191

Samply.MDR - A Metadata Repository and Its Application in Various Research Networks - Kadioglu, Dennis; Breil, Bernhard; Knell, Christian; Lablans, Martin; Mate, Sebastian; Schlue, Danijela; Serve, Hubert; Storf, Holger; Ückert, Frank; Wagner, Thomas; Weingardt, Paul; Prokosch, Hans-Ulrich (Studies in health technology and informatics, 2018)
Collaboration in medical research is becoming common, especially for collecting relevant cases across institutional boundaries. If the data, which is usually very heterogeneously formalized and structured, can be integrated, such a collaboration can facilitate research. An absolute prerequisite for this is an extensive description about the formalization and exact meaning of every data element contained in a dataset. This information is commonly known as metadata. Various research networking projects tackle this challenge with the development of concepts and IT tools. The Samply Metadata Repository (Samply.MDR) is a solution for managing and publishing such metadata in a standardized and reusable way. In this article we present the structure and features of the Samply.MDR as well as its flexible usability by giving an overview about its application in various projects.
EVALuna2:209468